2024
DOI: 10.3389/fimmu.2024.1328193
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying immunosuppression by regulatory cells

Oliver Goldmann,
Obiageli Vivian Nwofor,
Qian Chen
et al.

Abstract: Regulatory cells, such as regulatory T cells (Tregs), regulatory B cells (Bregs), and myeloid-derived suppressor cells (MDSCs), play a crucial role in preserving immune tolerance and controlling immune responses during infections to prevent excessive immune activation. However, pathogens have developed strategies to hijack these regulatory cells to decrease the overall effectiveness of the immune response and persist within the host. Consequently, therapeutic targeting of these immunosuppressive mechanisms dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 177 publications
(220 reference statements)
0
0
0
Order By: Relevance
“…Studies have indicated that IL-17 can stimulate the production of TNF-α and is implicated in the development of IR [ 36 ]. Regulatory T (Treg) cells constitute a minor subset of T lymphocytes known for their pivotal role in suppressing inflammatory responses [ 37 ]. During the progression of diabetes, Treg cells can inhibit Th1 and Th17 cell responses through the regulation of the microenvironment and alteration of surface receptor expression, consequently ameliorating IR [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that IL-17 can stimulate the production of TNF-α and is implicated in the development of IR [ 36 ]. Regulatory T (Treg) cells constitute a minor subset of T lymphocytes known for their pivotal role in suppressing inflammatory responses [ 37 ]. During the progression of diabetes, Treg cells can inhibit Th1 and Th17 cell responses through the regulation of the microenvironment and alteration of surface receptor expression, consequently ameliorating IR [ 38 ].…”
Section: Discussionmentioning
confidence: 99%